Election Law Enforcement: Fighting Black Campaigns on Social Media - Fikri, Sultoni (Amsir Law Journal, 2024)
The establishment of a democratic state requires the active involvement of its citizens, primarily through political participation, via elections. An integral part of elections is campaigning, which is inherently a strategy sometimes used to undermine opponents. These campaigns are known as “Black Campaigns”. It involves the use of malicious and unethical tactics aimed at discrediting political opponents. One method that is commonly used today is the dissemination of false information, which leads to slander that erodes the dignity, reputation, and honor of election participants. This study aims to evaluate the implementation of election laws and the management of negative political campaigns spread through social media platforms. Using normative legal research methodology, this research uses legal sources in the form of laws or other regulations, legal principles, and relevant doctrines. This research reveals that black campaigns are explicitly regulated in Article 280 of Law No. 7/2017 and Article 69 of Law No. 1/2015. This law categorizes black campaigning as a prohibited act, which includes insults, incitement, and threats against individuals. In the event of black campaigning on social media, the provisions outlined in Article 27 paragraph 3 and Article 28 paragraph 2 of Law No. 19/2016 should be enforced. To address the problem of black campaigns on social media, effective countermeasures need to be proposed, such as proactively promoting media literacy to coordinating its handling with relevant institutions. In addition, repressive measures including imposing legal sanctions on individuals involved in black campaigns on social media are also necessary. ___ References Books with an author: Soedarto. (1986). Hukum dan Hukum Pidana. Bandung: Alumni. Soekanto, S. (2004). Faktor-Faktor yang Mempengaruhi Penegakan Hukum. Jakarta: Rajawali Press. Soempeno, F. A. (2009). Prabowo dari Cijantung Bergerak ke Istana. Yogyakarta: Galangpress Group. Journal articles: Ardiansyah, M. K. (2020). Pembaruan Hukum oleh Mahkamah Agung dalam mengisi Kekosongan Hukum Acara Perdata di Indonesia. Jurnal Ilmiah Kebijakan Hukum, 14(2), 361-384. Azis, A., Sulfiyati, S., Putrawan, P., August, G., & Dinsar, A. (2023). Analisis Strategi Promosi Media di Kantor KPU Parepare. Jurnal Ilmiah Multidisiplin Amsir, 2(1), 145-154. Dodu, A. B. D. (2017). Regulasi Pemilu Terkait dengan Black Campaign dan Efektifitasnya Dalam Penindakan (Studi Kasus Pilkada Kabupaten Banggai Tahun 2015). JWP (Jurnal Wacana Politik), 2(1), 52-60. Doly, D. (2020). Penegakan Hukum Kampanye Hitam (Black Campaign) di Media Sosial: Pembelajaran Pemilihan Umum Presiden Tahun 2019. Kajian, 25(1), 1-18. Halimatusa’diah (2015). Etnisitas dan Agama Dalam Kontestasi Wacana Kekuasaan di Media Baru. Jurnal Masyarakat & Budaya, 17(2), 265-270. Hui, J. Y. (2020). Social Media and the 2019 Indonesian Elections: Hoax Takes the Centre Stage. Southeast Asian Affairs, 155-171. Januru, L. (2016). Analisis Wacana Black Campaign (Kampanye Hitam) pada Pilpres Tahun 2014 di Media Kompas, Jawa Pos dan Kedaulatan Rakyat. Natapraja, 4(2), 181-194. Kaimudin, A. (2019). Perlindungan Hukum terhadap Tenaga Kerja Anak Dalam Peraturan Perundang-Undangan di Indonesia. Jurnal Yurispruden, 2(1), 37-50. Mustawa, M., Hamid, A. H., & Purwanda, S. (2022). Refund of State Financial Losses in Realizing the Welfare State of Law. Amsir Law Journal, 4(1), 51-61. Nur, S. M., Syaputra, D., & Zainin, F. (2022). Tinjauan Yuridis Mengenai Black Campaign di Sosial Media. UNES Law Review, 5(2), 509-526. Pamungkas, A. D., & Arifin, R. (2019). Demokrasi dan Kampanye Hitam dalam Penyelenggaraan Pemilihan Umum di Indonesia (Analisis atas Black Campaign dan Negative Campaign). DIKTUM: Jurnal Syariah Dan Hukum, 17(1), 16-30. Prasetyoningsih, N. (2014). Dampak Pemilihan Umum Serentak bagi Pembangunan Demokrasi Indonesia. Jurnal Media Hukum, 21(2), 23. Punch, M., Crawshaw, R., & Markham, G. (2016). Democratic Principles and Police Fatal Force: Avoidance of Debate, Unresolved Accountability and Human Rights. International Journal of Law, Crime and Justice, 100(46), 2-12. Purwanda, S., & Dewi, M. N. K. (2020). The Effects of Monism and Pluralism on Legal Development of a Nation. Amsir Law Journal, 2(1), 21-26. Safitri, M. (2020). Problem Ujaran Kebencian (Hate Speech) di Media Sosial Perspektif Al-Qur'an. Al-Fath, 14(2), 203-238. Simamora, J. (2014). Tafsir Makna Negara Hukum dalam Perspektif Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Jurnal Dinamika Hukum, 14(3), 547-561. World Wide Web: Arbar, T. F. (2023). Pilpres RI Disorot Asing, Sebut Capres Anies Baswedan. Available online from: https://www.cnbcindonesia.com/news/20230809094413-4-461350/pilpres-ri-disorot-asing-sebut-capres-anies-baswedan Nur, M. F. (2024). Silang Sengkarut Dugaan Politik Bansos, Siapa yang Diuntungkan?. Available online from: https://tirto.id/silang-sengkarut-dugaan-politik-bansos-siapa-yang-diuntungkan-gT5U